2017
DOI: 10.1016/j.otsr.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Acute quadriceps tendon rupture repaired by suture anchors: Outcomes at 7 years’ follow-up in 25 cases

Abstract: IV, retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 32 publications
4
30
0
1
Order By: Relevance
“…[1][2][3][4][5]12,17,19 The standard of care is passage of nonabsorbable sutures through transosseous patellar bone tunnels, but repair with suture anchors has been studied as an alternative that allows for less tissue trauma, decreased operative time, safe early initiation of rehabilitation protocols, and reduced risk of patella fracture or damage. 3,7,[10][11][12][18][19][20]21,23 Despite these potential advantages, biomechanical studies have yielded inconsistent results regarding the superiority of suture anchor repair over repair with transosseous tunnels. 7,[10][11][12][18][19][20] We propose quadriceps tendon repair using the 4.75-mm biocomposite knotless suture anchor with tape suture technique as a biomechanically superior alternative to either transosseous tunnels or suture anchor repair alone, with significant advantages both in and out of the operating room.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5]12,17,19 The standard of care is passage of nonabsorbable sutures through transosseous patellar bone tunnels, but repair with suture anchors has been studied as an alternative that allows for less tissue trauma, decreased operative time, safe early initiation of rehabilitation protocols, and reduced risk of patella fracture or damage. 3,7,[10][11][12][18][19][20]21,23 Despite these potential advantages, biomechanical studies have yielded inconsistent results regarding the superiority of suture anchor repair over repair with transosseous tunnels. 7,[10][11][12][18][19][20] We propose quadriceps tendon repair using the 4.75-mm biocomposite knotless suture anchor with tape suture technique as a biomechanically superior alternative to either transosseous tunnels or suture anchor repair alone, with significant advantages both in and out of the operating room.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies of repair with transosseous patellar tunnels describe immobilization for 6 weeks after surgery, but there has been a recent push toward early motion. 7,13,23,24 Reported complications of extended immobilization include limited flexion, pain, weakness, decreased patellar mobility, and patella baja. 14 Studies have suggested that, while excessive loading can cause gap formation and weaken the repair, some controlled motion is necessary to heal the tendon 23,25 and reduce the risks of stiffness and atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard techniques used to repair QMF tendon rupture have some disadvantages 8,9 ; they lack sufficient strength to permit patients to exercise the full range of motion. There is no consensus regarding rehabilitation protocol.…”
Section: Clinical Problemsmentioning
confidence: 99%
“…However transosseous sutures and anchor fixation are the most well described when dealing with ruptures at the tendon-bone junction. Since being reported in the mid 1950's (12), using transosseous sutures to reinsert the tendon through patella drill holes has remained the primary option when dealing with QTR (1,13). The use of suture anchors drilled into the patella when reinserting the quadriceps tendon(QT) was first described in year 2000 by Maniscalco et al (14).…”
Section: Introductionmentioning
confidence: 99%